DO PRECONCEITO À (IM)POLIDEZ: ASPECTOS SOCIAIS, IDEOLÓGICOS E LINGUÍSTICOS QUE CIRCUNSCREVEM PRÁTICAS RACISTAS E SEXISTAS NO FACEBOOK - Feitosa e Paiva, Geórgia Maria; Martins Oliveira da Silva, Tatiana (Cadernos de Linguagem e Sociedade, 2019)
Virtual interactions are often an extension of face-facing encounters, solidifying in digital spaces as the discursive discourse of racism and sexism practices. Starting from the studies of Sociology, Pragmatics and Interactional Sociolinguistics, our goal is to understand, from Fanon (2008), Van Dijk (2017) Brown and Levinson (1987) and Culpeper (1996; 2011), as the prejudice of materializing in (im) language policy through Facebook posts. We conducted a qualitative, exploratory and descriptive survey whereby we selected a post in a Facebook group about a possible case of harassment between a foreign student and a brazilian student. For this, it selects and analyzes as the most relevant answers, according to the criteria of the social network itself. The results demonstrated how politeness strategies were used both to create a positive image of the potential offender and to solicit support from group members in relation to him; In addition, there is condensation between politeness and impoliteness strategies when the effect was to attack one of the group members, the victim or the supposed aggressor himself. Our investigation shows the historical, ideological, social and contextual foundations for the event, as well as an analysis of the politeness and impoliteness strategies applied by the group participants. Conclude that the statements seek alternate between politeness and linguistic impoliteness for the production of biased messages.